(untitled) (Perspectivas de las Ciencias Económicas y Jurídicas, 2026)
In a global system where personal information has become an invaluable resource, data protection is a priority on international agendas in light of the advance of big data, data mining, and the resulting violation of rights. This paper aims to highlight trends, patterns, and possible shortcomings in the protection of personal data through an analysis of cases of the Supreme Court of Justice of the Nation of Argentina.